Healthcare homes and resort hotels of the Christian National Association of Common School Teachers in the interwar period - Zagdańska, Joanna (Studia Ecologiae et Bioethicae, 2018)
The years of partitions, especially the period of the First World War, caused considerable deterioration of the health of the Polish population. The situation required radical action and heavy financial expenses. Meanwhile, the newly reborn Polish state had very few resources to provide fully professional healthcare. Therefore, different types of working professionals were expected to participate in the nationwide fight for citizens’ health and leisure. The first Polish community which strongly supported the Polish government in this area were teachers grouped in several organisations and associations. Among them was the Christian National Association of Common School Teachers, created in September 1921 as a result of the merger of nine teacher organisations. The result of the voluntary taxation of the representatives of that patriotic and national organisation was the establishment and maintenance of healthcare homes in Sewerynówka, near Szczawnica, and in Zakopane, as well as the resort hotel in Jastrzębia Góra. Some of these centres are still functioning.